Tree-ring record in Ethiopian church forests reveals successive generation differences in growth rates and disturbance events. - Hailu, Abrham Abiyu; Mokria, Mulugeta; Gebrekirstos, Aster; Bräuning, Achim (Forest Ecology and Management, 2018)
Forests provide fundamental ecosystem services. Environmental changes are predicted to affect forest growth directly through increased environmental stressors, and indirectly by amplifying disturbance. To increase our understanding of effects of environmental changes and disturbance on Afromontane forest growth, we used tree-ring data collected from Juniperus procera trees from church forests in the northwest highlands of Ethiopia. We used structural change models to detect structural shift in growth trends. We applied Linear Mixed Effect Models (LMM) to compare growth rate differences between successive tree generations. The running mean method and radial growth pattern analysis were used to detect disturbance events. Three groups of generations were identified based on Basal Area Increment (BAI) rates. There are significant differences (χ2 = 204.64, P < .001) among generations in pace of BAI, indicating that old generation trees grew at a slower pace than younger ones. Radial growth patterns were homogeneous for the old generation, but diverse in young trees. The observed high growth rates in the younger generation may have a negative effect on the longevity of the individuals and positively affect carbon accumulation in the biomass. Disturbance was detected in all generations, but worsened in the 20th century. About 35% of disturbances matched with climate extreme events, providing evidence that the disturbance is both human-induced (i.e., site-specific) and climate-induced. Thus, forest management plans should emerge from a sound understanding of climate-forest-human interactio